Sink ? Source System of In vitro Suspension Culture of Celastrus paniculatus under Regulation of Monochromatic Lights (Plant Tissue Culture and Biotechnology, 2016)
Plants are wonderful resource of bioproducts encompassing significant value to medicines and drug development. The plant cell suspension cultures bear immense potential for production of high?value secondary metabolites and are chosen as alternative sources of raw material for industrial use. In the present study, homogenous cell suspension culture of Celastrus paniculatus a medicinally important plant was established and multifold production of alkaloids and total phenols was obtained under the influence of monochromatic lights. One month old leaf derived friable callus of C. paniculatus was used to raise homogenous suspension culture and kept on rotary shakers in cabinets illuminated with different monochromatic LED lights (Blue, Yellow and Red). The monochromatic lights proved to be a strong abiotic elicitor in driving the production of secondary metabolites so much so that the metabolites were released extracellularly and the medium served as sink or spacious pool for leaked out metabolites from the cell mass. Maximum production and enhancement in alkaloids and phenols (98 and 44.7%, respectively) over control was obtained from cell mass grown under yellow light treatment, followed by blue (64 and 23.7%) and red light (50 and 26%) treatments. Further scale up of secondary metabolite production was hence performed under yellow light conditions, starting from 2.5 gm cell mass suspended in 250 ml of media extended up to 1000 ml culture media for one month. The continuous culture system exhibited remarkable potential of this plant cell system as multifold yield of total alkaloids (91.69 ?g/1750 ml) and phenols (70.59 ?g/1750 ml) was obtained during 30 days of culture under yellow light conditions. The production was remarkably enhanced by 100?folds (5.29 to 48.21 ?g; Fig. 2) for alkaloids and 70?folds (1.73 to 46.33 ?g; Fig. 3) for phenols, from zero days to 30?day?old culture phase. Hence, strategic implementation of monochromatic lights holds great promises for controlled commercial production of myriads of valuable secondary metabolites from plant cell cultures of important medicinal plants. Present work contributes to the first reports where continuous, enhanced, multifold yield of important secondary metabolites were obtained from cell suspension culture of Celasrus paniculatus an endangered medicinal plant.Plant Tissue Cult. & Biotech. 26(2): 175-185, 2016 (December)